The Influence of Quality of Work Life on Individual Commitment in Organizations Mediated by Self-Efficacy: A Study on Teachers at Islamic High School in Malang City - Danni Marindra; Adya Hermawati; Alfiana (Journal of Management Research and Studies, 2026)
This research is motivated by the low level of teacher commitment and a lack of ownership towards their workplace. Based on an initial survey conducted by the researcher on 37 teachers at SMA "ISLAM" Malang, it was found that 62% (22 teachers) felt they received insufficient support from the school in professional development. In addition, 38% (14 teachers) admitted to having thought about moving to another school in the last 2 years. The research used by the author is an explanatory or explanatory research type, with a quantitative approach. In this study, the population used was all 37 teachers who teach at SMA "ISLAM" Malang, for the research sample that the author used was less than 100 people. The sampling technique was taken from the entire population, because the population was less than 100 people, using a random sampling technique or random sampling. The results of the research obtained in this article are that there is a positive contribution of quality of work life to the variables of individual commitment and self-efficacy, and self-efficacy also has a positive contribution to individual commitment. In addition, self-efficacy also plays a strong mediating role in the quality of work life towards individual commitment of teachers at SMA “ISLAM” Malang.